The Influence of Sports Celebrities’ Brand Personality on Celebrity Identification and Consumers’ Intention to Buy the Endorsed Brands - Shezi, Nkosinamandla (Acta Universitatis Danubius. Œconomica, 2025)
Celebrity endorsement is becoming very popular, especially in sports. The purpose of this study was to determine the influence of sport celebrities’ brand personality on sport celebrity identification and consumers’ intentions to buy the endorsed brands. A descriptive research design and quantitative method were employed in the study. The participants of the study were drawn from Generation Y consumers in South Africa. The results of the study show that the attributes of “sophistication”, “sincerity” and “classic” positively influence sport celebrity identification. Furthermore, the results indicate that sport celebrity identification positively influences purchase intentions of the endorsed brands. It was found that “sophistication” is the most important factor that influences sport celebrity identification, followed by the attributes of “classic” and “sincerity”. The study offers recommendations for the brand personality of a sport celebrity and suggests ways to influence sport celebrity identification and purchase intentions with regard to endorsed brands.